E-107 Predictors of decompressive hemicraniectomy in successfully recanalized patients with anterior circulation emergency large vessel occlusion. (4th August 2020) - Goyal, N; Tsivgoulis, G; Pandhi, A; Ishfaq, M; Goyanes, J; Deep, A; Alsbrook, D; Singh, S; Zaid, G; Hoit, D; Nickele, C; Inoa, V; et al.
Abstract : Background and Purpose: Mechanical thrombectomy (MT) is demonstrated to improve functional outcome of patients with anterior circulation strokes with emergency large vessel occlusion (ELVO). Despite successful recanalization (SR), a proportion of these patients require decompressive hemicraniectomy (DHC). We aimed to study the predictors of DHC in successfully recanalized anterior circulation ELVO patients. Methods: Consecutive anterior circulation ELVO patients treated with MT during a 6-year period in a tertiary stroke center were evaluated. Only patients with SR (mTICI 2b, 2c or 3) after MT were included in the analysis. Baseline demographic, clinical and procedural variables were compared between the patients who required DHC after successful recanalization vs. who did not. Collaterals for anterior circulation ELVO (ie, poor (collateral score=0) vs. good (collateral score=1, 2 and 3) were reported using a methodology that has been shown to predict clinical outcome. Good functional outcome was defined as mRS score of 0–2 at 3 months. Univariable and multivariable logistic regression analyses were used to determine the predictors of DHC. Results: Of 453 successfully recanalized anterior circulation ELVO patients, 47 underwent DHC (mean age 58±13 years, 53% male, median admission NIHSS-score: 17 points, IQR 13–21). The patients in DHC group were younger in age (mean age in years±SD; 58±13 vs. 65±15, p=0.004), had higher admission systolic blood pressure (mmHg: 167±33 vs. 155±30, p=0.010), higher admission diastolic blood pressure (mmHg: 95±28 vs. 87±19, p=0.019), higher admission blood glucose levels (mg/dl: 170±88 vs. 142±66, p=0.008), similar median admission NIHSS (17 (IQR: 13–21) vs. 15 (IQR: 11–20), p=0.087), lower median ASPECTS (9 (IQR: 8–10) vs. 10 (IQR: 9–10), p=0.002), and poor collaterals on pre-treatment CT angiogram (% with poor collaterals: 75% vs. 26%, p<0.001) compared to those who did not required DHC. The DHC group required more passes during MT (median: 3 (IQR: 3–4) vs. 2 (IQR 1–2), p=0.001), had longer groin puncture to recanalization time (mean: 74±32 vs. 55±35, p<0.001), while no difference was seen in symptoms onset to groin puncture time (mean: 313±166 vs. 304±202, p=0.784) compared to the non-DHC group. The patient in DHC group tended to have a higher sICH rate (15% vs. 7%, p=0.20), higher 3 months mortality (41% vs. 16%, p=0.001) and lower rates of good functional outcome at 3 months (26% vs. 58%, p=0.001). In multivariable model after adjusting for various confounders, higher blood glucose levels on admission (OR per 1 mg/dL increase: 1.01; 95% CI: 1.00–1.01, p=0.031), poor collaterals on CT angiography (OR: 0.13; 95% CI: 0.05–0.32, p<0.001), and higher number of passes during MT (OR per 1 pass increase: 4.84; 95% CI: 3.09–7.58, p<0.001) emerged as independent predictors of DHC in successfully recanalized ELVO patients. Conclusion: Higher blood glucose levels on admission, poor collateral pattern on CT angiography and higher number of passes during MT were independently associated with DHC in anterior circulation EVLO patients achieving SR at the end of MT. Of these, admission glucose levels and number of passes during MT are potentially modifiable factors. Disclosures: N. Goyal: None. G. Tsivgoulis: None. A. Pandhi: None. M. Ishfaq: None. J. Goyanes: None. A. Deep: None. D. Alsbrook: None. S. Singh: None. G. Zaid: None. D. Hoit: None. C. Nickele: None. V. Inoa: None. D. Dornbos: None. A. Alexandrov: None. A. Arthur: None. L. Elijovich: None.